Uma análise jurídica da efetividade das normas ambientais aplicáveis a produção das matérias-primas dos biocombustíveis - Batista, Jéssica de Araújo (2014)
This work has as its central point the investigation of environmental juridical regulatory situation in Brazil correlated to the problem of effectiveness of environmental regulations in the phase of agricultural cultivation of raw materials for biofuels. In developing this theme was observed four events that are related: the rise of biofuels in their energetic matrix; the expansion in the use of natural resources to cultivate the raw materials of this energy source; the need for environmental standards applicable to the agricultural cultivation of biofuels are functional and effective; and the occurrence of environmental damage agricultural arising from the chaotic use of natural resources for the production of raw materials for biofuels. Considering this situation, was made an investigation about the limits of the environmental regulation of the cultivation of raw materials of biofuels, and about previous and posterior stage of formation of environmental laws, with the purpose of responding which aspects influence and may form barriers to the effectiveness of environmental standards in each of these phases, and also how these obstacles can be eliminated. To do this was analyzed, based on Legisprudence, the previous stage to do new laws, and were also analyzed some constitutional articles and infraconstitutional laws related to the theme. Moreover, were also analyzed some environmental competencies, the legislative power of entities of government, and instruments of intervention government in agricultural economics in favor of environmental. After these analyzes, it was found some defects in the environmental regulation of agrofuels, that have direct influence on the functionality and effectiveness of constitutional principles and on the environmental laws. So, it was concluded, that there is need improvements in the previous stage of formation of environmental laws, related, for example, with the work of Legislative Power and with the use techniques of legistics for creating of adequate laws, and was also showed the need to improve environmental laws and its scenery in specifics points, to effect the sustainable development that result of economic success and of protection of natural resources. In summary, it was concluded that it is need an appropriate environmental management, to work in four perspectives: produce effective laws; creating a structural apparatus in accordance with the environmental regulation, and that function in the reality; effect government decisions; encourage enforcement of environmental laws, of government decisions, and of Constitution of 1988. These four perspectives will add up and will have as a consequence a reduction in levels of environmental degradation in the first stage of the production chain of biofuels, protecting the natural resources.